GAGASAN PENGATURAN PERIZINAN OJEK ONLINE DIKAITKAN DENGAN UPAYA PERLINDUNGAN HUKUM TERHADAP WARGA NEGARA - M. Haikal Rahman; Emilda Firdaus; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Transport types of motorcycles or motorcycle called online does not have permissions in the field of public transport. Online motorcycle taxi is public transportation by using a motorcycle as a means to transport it using the app liaison between the riders and their users or based technology. The existence of this online motorcycle is quite prevalent at the present time, but the licenses have not been included in the regulations in Indonesia. As in Law Number 22 of 2009 on Traffic and Transportation motorcycles only included into the personal or individual transport. Not included in the public transport, because the means of transport is used not only to one person but to many people.This type of research can be classified ie normative legal research done by researching library materials or secondary data as the base material for examination by doing a search on the regulations and literature relating to the cases studied. This research was conducted by means of an idea initiated the idea for the creation of a licensing regulations to provide legal protection to every citizen. The data sources used, the primary data, secondary data and data tertiary, data collection techniques in this study with the study of literature, and take ktipan of supporting literature.In the research the problem there are two things that can be inferred. First, online motorcycle licensing arrangements associated with the legal protection of citizens, related to all aspects of protection. Secondly, the idea pengatururan online motorcycle license to provide legal protection to citizens, re-evaluate all aspects relating to motorcycles online and make revisions to Act No. 22 of 2009 on Road Traffic and Transport.Keywords: Ideas, Licensing, Taxibike online, Legal Protection